Analiza normativnih ukrepov za zaščito virov pitne vode pred negativnimi vplivi s cest - Brenčič, Mihael (Acta hydrotechnica, 2001)
Slovenia has a number of drinking water resources, with their protected water recharge areas extending over a large part of the Slovenian territory. Consequently, roads and traffic often run within these areas, and are subject to numerous restrictions imposed by drinking water resource protection regulations. This article gives an analysis of these regulations and divide them into six groups: restrictions of road and manoeuvring area construction, technical and engineering requirements for ground water protection, traffic speed restrictions, restrictions of transit transport, restrictions of the transport of dangerous and harmful substances, and requirements for setting up traffic signs. The properties of each group are briefly described and analysed, and the representation of each group in the analysed water protection acts is given.
Keywords: ceste; pitna voda; podtalnica; vodni viri; vplivi; zaščita